EFEKTIVITAS BELIMBING WULUH (Averrhoa bilimbi) DALAM MEMPERTAHANKAN KESEGARAN IKAN KEMBUNG (Rastrelliger kanagurta) SELAMA PENYIMPANAN DINGIN - Huda, Saiful; Surti, Titi; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Bilimbi (Averrhoa bilimbi) is a natural medicinal herbs that containing flavonoid compoundsthat act as antimicrobials. However, the utilization of bilimbi (Averrhoa bilimbi) has not beenwidely applied. The purpose of this study was to determine how effective bilimbi (Averrhoabilimbi) to maintain freshness mackerel (Rastrelliger kanagurta) fresh during cold storage.The results showed that the extracts bilimbi and storage time influence on organoleptic, TPCtest, and TVBN test. Organoleptic test results in the treatment of fish: ice bilimbi extract 1:1(B1) with 4.5% can be accepted until day-11 with an average value of 7,11. TPC test resultsin the treatment of fish: ice 1:1 (B1) and 3:1 (3:1) with bilimbi extract 4.5% can be accepteduntil the day of 9 with bacterial counts each 1.93 x 104 Cfu/g and 3.00 x 104 Cfu/g. Testresults on the treatment TVBN fish: ice 1:1 (B1), 3:1 (B2) , and 5:1 (B3) respectively withbilimbi extract 4.5% is still acceptable until day-12 with a value of 14.57 mgN%, 15.64mgN%, and 15.90% mgN%. Bilimbi (Averrhoa bilimbi) proved effective in maintaining thefreshness of the mackerel (Rastrelliger kanagurta) during cold storage